Knowledge, attitude and practice towards blood donation among health sciences students of Universiti Kebangsaan Malaysia - Mohamad Anuar, Nur Najmi; Gan, Wen Xin; Zulkafali, Nurul Iman Natasya; Yusof, Nur Aini; Jaffar Ali, Muhamad Norizwan; Salim, Noor Idaya; Ibrahim, Norul Hasmida; Subramaniam, Valarmathie; Taib, Izatus Shima (Life Sciences, Medicine and Biomedicine, 2020)
Introduction: Increased demand and low blood supply have been a critical issue in many countries, including Malaysia. This issue occurs due to a lack of awareness towards the importance of blood donation. Therefore, this study aims to evaluate the level of knowledge, attitude and practice towards blood donation among undergraduate students of the Faculty of Health Sciences (FSK), Universiti Kebangsaan Malaysia (UKM), Kuala Lumpur. Methods: This cross-sectional study was conducted on undergraduate students of the Faculty of Health Sciences (FSK), Universiti Kebangsaan Malaysia (UKM), Kuala Lumpur, which is comprised of 9 programmes: Biomedical Science, Optometry, Nutrition Science, Dietetics, Audiology, Speech Science, Physiotherapy, Occupational Therapy and Environmental Health. The respondents were recruited by a stratified random sampling technique with an informed consent. Questionnaire that consisted of four sections, namely: (A) sociodemographic characteristics, (B) knowledge on blood donation, (C) attitude towards blood donation and (D) practice of blood donation were distributed and a total of 274 responses were obtained for further evaluation. The significance values were set as P < 0.05. Results: Our research findings showed that the majority of students had a good level of knowledge (99.6%) and attitude (95.3%) about blood donation but most of them demonstrated a poor practice (59.1%). As for genders, female students had a better level of knowledge and attitude than males, but male students committed better practice towards blood donation than females. However, there were no significant differences between gender and programme of study as the respondents shared a similar background in health-related courses. Conclusion: A majority of the students had a good level of knowledge and attitude, but they are poor in practice. More campaigns need to be conducted to create awareness on the importance of blood donation.